Gimkit Media Strategy in UbD-Based Classroom Services to Improve Students' Time Management Skills - Harahap, Rahmadani; Rizka Harfiani; Irsyad Mubarak (INDONESIAN COUNSELING AND PSYCHOLOGY, 2025)
This research departs from the problem of students' low time management skills which have an impact on learning disorganization, habit of postponing tasks, and lack of discipline. Therefore, the researcher integrated three main components, namely Gimkit media, classical guidance services, and Understanding by Design (UbD) approach as an intervention strategy to improve students' time management skills. The purpose of this study was to determine whether the gimkit media strategy in UbD-based classical services can improve students' time management skills. The research method used is classroom action research in the form of a spiral cycle consisting of planning, acting, observing, and reflecting stages. The sample was students of class X.10 of State Senior High School 3 Medan. Data were analyzed using the percentage formula. The results showed a significant increase in students' time management skills after participating in classical guidance services designed using the Understanding by Design (UbD) approach and Gimkit interactive media. This can be seen from the increase in the average score of the questionnaire from 23.6 in the pre-cycle to 36.2 in cycle III, as well as the increase in the number of students in the “Good” and “Very Good” categories from 11% to 95%. Gimkit media effectively increased student engagement in the service process. Classical guidance services as a group coaching medium proved to be able to create a reflective and solutive learning atmosphere. Through discussion, open reflection, and evaluation of personal commitment, students showed awareness and changes in mindset and behavior towards time management.